IMPLEMENTASI LARASITA (LAYANAN RAKYAT SERTIPIKAT TANAH) SEBAGAI UPAYA PENINGKATAN KUALITAS PELAYANAN PUBLIK - DEWI SIMBOLON , Endang Sri Santi, Suhartoyo*) (Diponegoro Law Journal, 2013)
Registration of land is an important issue in the BAL and as a means for the government to collect data over a land rights for all land in the territory of the Republic of Indonesia and not be a clear ownership wastelands also avoid chaos in the control of land rights, land registration is due early of the birth of a proof of ownership of land. Basic Agrarian Law and the mandate of Article33 paragraph (3) of the 1945 Constitution embodied the built and developed LARASITA that depart from the will and motivation to get closer with the National Land Agency, as well as changing the paradigm of the principal duties and functions of the BPN wait or passive to active or proactive (Introduction Regulation of  Head of National Land Agency of the Republic of Indonesia No.. 18Year 2009 About LARASITA BPN_RI). The problems are formulated, namely the implementation of How  People  Services Land  Certificate (LARASITA) by Jatipurwo Village Land  Office, District Rowosari,  Kendal and was with the People's Service Certificate Program Land (LARASITA) can improve the quality of public services for rural Jatipurwo, District Rowosari, KendalApproach  method  is  empirical  juridical  approach,  the  specification  using  descriptiveanalytical  research,  while  the  population  of  all  parties  associated  with  the  implementation LARASITA program and sampling methods are purposive sampling is done by taking the subject and the object based on the specified destination. The data collection methods the authors use the technique of interviewing her (interview) and based on existing data (primary and secondary) that have been collected to allow for qualitative data analysis.Based  on  the  results  of  the  study  showed that  the  implementation of  the  land through Program LARASITA certificated Village Jatipurwo managed and implementation services provided by the District Land Office Kendal in accordance with the Service Standards and Regulation in the Land Act No. 25 of 2009. This can be evidenced by the level of public satisfaction with the services provided so that the number of applicants who want certificated the land with increased LARASITA Program.Implementation LARASITA in  District  Rowosari  Village  Jatipurwo generally  went  well, successful and have high levels of citizen satisfaction are quite satisfied with the service provided both the BPN-RI Land Kendal and the village in charge of running the Program Larasita Jatipurwo village which has a  number  of applicants to follow the growing Larasita Program. To further provide more baih longer required continuous extension and additional car LARASITA.